2020
DOI: 10.25225/jvb.20014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and origins of invasive black rats (Rattus rattus) in Benin, West Africa

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The Republic of Benin, formerly Dahomey, is located in West Africa, surrounded by Togo, Nigeria, Burkina Faso and Niger. Currently, Benin has an important maritime commerce through its International Sea port of Cotonou [ 17 ] with importation of vehicles, rice, fuels and palm oil ( https://www.tresor.economie.gouv.fr/Pays/BJ/commerce-exterieur-du-benin ) and exportation of raw cotton (34.5% of exportations), coconuts, Brazil nuts and cashews and gold to, inter alia, India, Bangladesh, China, United Arab Emirates and Vietnam ( oec.world/en/profile/country/ben/ ).…”
Section: Introductionmentioning
confidence: 99%
“…The Republic of Benin, formerly Dahomey, is located in West Africa, surrounded by Togo, Nigeria, Burkina Faso and Niger. Currently, Benin has an important maritime commerce through its International Sea port of Cotonou [ 17 ] with importation of vehicles, rice, fuels and palm oil ( https://www.tresor.economie.gouv.fr/Pays/BJ/commerce-exterieur-du-benin ) and exportation of raw cotton (34.5% of exportations), coconuts, Brazil nuts and cashews and gold to, inter alia, India, Bangladesh, China, United Arab Emirates and Vietnam ( oec.world/en/profile/country/ben/ ).…”
Section: Introductionmentioning
confidence: 99%
“…The cytb region of the mitochondrial genome haplotypes were extracted using MEGA7, and combined with modern cytb haplotypes from previous publications 10,24,69,70 and this study. We aligned the data using MAFFT v7.123b 125 , then built a ML tree using RAxML v8.2.9 124 , with GTR+I+G model and 1000 bootstrap replicates.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…In order to establish the relationship between the ancient rats and modern black rats from across their range, we analysed the cytochrome b (CYTB) region from our ancient samples alongside 132 previously unpublished modern CYTB sequences from across the Indian Ocean basin (Supplementary Table 9), and sequences published in previous studies 10,24,69,70 . The maximum likelihood tree of the CYTB region revealed that all the ancient rats from this study belong to the previously described black rat lineage I (Figure 2 , Supplementary Figure 4, 5 and Table 10).…”
Section: A Global Phylogeography Of the Black Rat Based On Mitochondrial Dnamentioning
confidence: 99%
“…For instance, the brown rat showed at least 13 evolutionary clusters globally [ 4 ]. Several evolutionary factors, such as climate and geography, predators, urbanization, and agricultural settlement, are behind these evolutionary changes [ 5 , 6 , 7 ]. The desert environment is also a factor for the phenotypic and genotypic evolutionary change of mammals.…”
Section: Introductionmentioning
confidence: 99%